Two‐drug antiretroviral regimens: an assessment of virologic response and durability among treatment‐experienced persons living with HIV in the OPERA® Observational Database. Issue 12 (4th December 2019) - Pierone, Gerald; Henegar, Cassidy; Fusco, Jennifer; Vannappagari, Vani; Aboud, Michael; Ragone, Leigh; Fusco, Gregory
Abstract: Introduction: Two‐drug regimens (2‐DR) have the potential to be a viable solution to the challenges of treatment complexity, cost, adverse effects and contraindications. We sought to describe the real‐world use and effectiveness of 2‐DR among persons living with HIV (PLHIV) in the United States. Methods: We analysed data for 10, 190 treatment‐experienced patients from the OPERA® Observational Database initiating a new 2‐DR or three‐drug regimen (3‐DR) between 1 January 2010 and 30 June 2016. Multivariate Cox Proportional Hazards models were used to estimate the association among 2‐DR or 3‐DR initiation and virologic suppression (viral load (VL) <50 copies/mL), virologic failure (2 VLs > 200 copies/mL or 1 VL > 200 copies/mL + discontinuation) or regimen discontinuation. Results: Patients initiating a 2‐DR (n = 1337, 13%) were older, and more likely to have a lower CD4 count, a history of AIDS and comorbid conditions than patients initiating a 3‐DR. There was no difference between groups in time to virologic suppression (aHR: 1.00 (95% CI: 0.88, 1.13)) among viraemic patients (baseline VL ≥ 50 copies/mL, n = 4180), or time to virologic failure (aHR: 1.15 (95% CI: 0.90, 1.48)) among virologically stable patients (baseline VL < 50 copies/mL, n = 6010). However, time to discontinuation was shorter following 2‐DR than 3‐DR initiation (aHR: 1.51 (95% CI: 1.41, 1.61)). Conclusions: In this large cohort of treatment‐experienced patients, 2‐DR prescriptions were common and more frequent among patients with significant comorbidity. Virologic response was similar, but duration of use was shorter with a 2‐DR than a 3‐DR, suggesting that 2‐DRs may be a virologically effective treatment strategy for treatment‐experienced PLHIV with existing comorbidities.